Reparación integral en las víctimas en el tráfico ilícito de migrantes. - Chávez Cobeña, Martha Elena (2025)
In Ecuador, legislation recognizes the need for comprehensive reparations for victims of migrant trafficking, but its implementation faces significant challenges. This research addresses the issue of comprehensive reparations by evaluating the effectiveness of Article 213 of the Comprehensive Organic Criminal Code (COIP) and analyzing its application in a notable case that highlights deficiencies in justice and protection measures. The main objective of this study was to assess how effectively the Ecuadorian regulatory framework provides comprehensive reparations to victims of migrant trafficking and to propose improvements in its application to ensure justice and rights for those affected. The research employed dogmatic, historical, and descriptive legal methods, utilizing a non-experimental design and conducting interviews with judges, prosecutors, and attorneys specializing in criminal law. Additionally, it included an analysis of rulings and current regulations. The findings revealed that victims do not receive adequate comprehensive reparations, as Ecuadorian regulations primarily focus on economic compensation while neglecting crucial measures such as psychological rehabilitation, social reintegration, and guarantees of non-repetition. Furthermore, the lack of international cooperation and existing institutional weaknesses hinder the fight against trafficking networks. In conclusion, the research indicates that comprehensive reparations in Ecuador are inadequate. It recommends strengthening legislation, providing training for justice officials, and establishing comprehensive support mechanisms for victims. Ultimately, the study emphasizes the importance of aligning regulations with international standards and enhancing coordination among institutions to combat this crime effectively.